Teachers’s Stimulation on Early Childhood Speech Delay at PAUD Kasya Banda Aceh - Siti Naila Fauzia; Nella Rahim; Dina Amalia; Sitti Muliya Rizka; Indani Indani (Early Childhood Education & Parenting, 2024)
Teacher stimulation is an action in learning by using various ways of teaching. Speech delay is a delay in the level of speech development with the child's age. The purpose of the study is to determine the teacher's stimulation in overcoming speech delay in early childhood. This research uses a qualitative approach, with a case study. Data was collected through observation and interviews. The research subjects were the principal, the therapist teacher, two classroom teachers, and two parents. The results obtained, teacher’s stimulation include communication strategies, environmental therapy, talk therapy, and the Kayang method.